Bariatric surgery and calcifediol treatment, Gordian knot of severe-obesity-related comorbidities treatment - Herrera-Martínez, Aura D.; Castillo-Peinado, Laura L. S.; Molina-Puerta, María J.; Calañas-Continente, Alfonso; Membrives, Antonio; Castilla, Juan; Camacho Cardenosa, Marta; Casado-Díaz, Antonio; Gálvez-Moreno, María A.; Gahete, Manuel D.; Quesada Gómez, José Manuel; Bouillon, Roger; et al. (Frontiers in Endocrinology, 2023)
Background: Obesity (OB) is a chronic metabolic disease with important associated comorbidities and mortality. Vitamin D supplementation is frequently administered after bariatric-surgery (BS), as to reduce OB-related complications, maybe including chronic inflammation.Aim: To explore relations between vitaminD metabolites and components of the inflammasome-machinery in OB before and after BS, and their relations with the improvement of metabolic comorbidities. Patients and methods: Epidemiological/clinical/anthropometric/biochemical evaluation was performed in patients with OB at baseline and six-months after BS. Evaluation of: i) vitamin-D metabolites in plasma, and ii) components of the inflammasome-machinery and inflammatory-associated factors [NOD-like-receptors (NLRs), inflammasomeactivation-components, cytokines and inflammation/apoptosis-related components, and cell-cycle and DNA-damage regulators] in peripheral blood mononuclear-cells (PBMCs), was evaluated at baseline and six-months after BS. Clinical and molecular correlations/associations were analyzed. Results: Significant correlations between vitamin D metabolites and inflammasomemachinery components were observed at baseline, and these correlations were significantly reduced six months after BS in parallel to a decrease in inflammation markers, fat mass and body weight. Treatment with calcifediol remarkably increased 25OHD levels, despite 24,25(OH)2D3 remained stable after BS. Several inflammasome-4 machinery components were associated with improvement in metabolic comorbidities, especially hypertension and dyslipidemia. Conclusion: The beneficial effects of vitamin D on OB-related comorbidities after BS patients are associated with significant changes in the molecular expression of key inflammasome-machinery components. The expression profile of these inflammasome components can be dynamically modulated in PBMCs after BS and vitamin D supplementation, suggesting that this profile could likely serve as a sensor and early predictor of the reversal of OB-related complications after BS.